Incidence of panic disorder in patients with non-cardiac chest pain and panic attacks. (June 2021) - Heppell, Jenny-Lee; Denis, Isabelle; Turcotte, Stéphane; Fleet, Richard P; Dionne, Clermont E; Foldes-Busque, Guillaume
This study documented the 6-month incidence of panic disorder and its predictors in emergency department patients with panic attacks and non-cardiac chest pain. The assessment included a validated structured interview to identify panic attacks and questionnaires measuring the potential predictors of panic disorder. Presence of panic disorder was assessed 6 months later. The incidence of panic disorder was 10.1 percent ( n = 14/138). Anxiety sensitivity was the only significant predictor of the incidence of panic disorder (odds ratio = 1.06; 95% confidence interval = 1.01–1.12). Patients with panic attacks and non-cardiac chest pain are at an elevated risk for panic disorder. This vulnerability appears to increase with anxiety sensitivity.